Cover Picture: Exploring the Potential Energy Surface of E2P4 Clusters (E=Group 13 Element): The Quest for Inverse Carbon‐Free Sandwiches (Chem. Eur. J. 16/2014). Issue 16 (14th April 2014) - Castro, Abril C.; Osorio, Edison; Cabellos, José Luis; Cerpa, Erick; Matito, Eduard; Solà, Miquel; Swart, Marcel; Merino, Gabriel
<x xml:space="preserve">Abstract</x> A viable alternative sandwich structure is presented, which does not contain any carbon atom. This D4h‐symmetric inverse sandwich instead uses the "carbon‐like" phosphorus, which together with heavier elements of Group 13 (E = Al–Tl) forms a stable molecule. Density functional theory computations indicate that the sandwich form is more stable than a D2d isomer of two perpendicular EP2 units (except for E=B), and should be formed exothermically from white phosphorus and E2. For more details, see the Full Paper by M. Swart, G. Merino et al. on page 4583 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>